Correlation between Use of Antiretroviral Adherence Devices by HIV-infected Youth and Plasma HIV RNA and Self-reported Adherence - Saberi, Parya (AIDS Behav, 2015)
Our objective was to investigate antiretroviral adherence device use by HIV-infected youth and assess associations of device use with viral suppression and self-reported adherence. This cross-sectional, multisite, clinic-based study included data from 1,317 HIV-infected individuals 12-24 years of age that were prescribed antiretroviral therapy. Mean adherence in the past seven days was 86.1% and 50.5% had an undetectable HIV RNA. Pillbox was the most commonly endorsed device. No specific device was independently associated with higher odds of 100% adherence. Paradoxically, having an undetectable HIV RNA was inversely associated with use of adherence devices (OR=0.80; p=0.04); however, among those with <100% adherence, higher adherence was associated with use of one or more adherence devices (coefficient=7.32; p=0.003). Our data suggest that adolescents who experienced virologic failure often used adherence devices which may not have been sufficiently effective in optimizing adherence. Therefore, other tailored adherence-enhancing methods need to be considered to maximize virologic suppression and decrease drug resistance and HIV transmission.